Protective effects of bestatin in the retina of streptozotocin-induced diabetic mice. (August 2016) - Hossain, Ahamed; Heron, David; Davenport, Ian; Huckaba, Thomas; Graves, Richard; Mandal, Tarun; Muniruzzaman, Syed; Wang, Shusheng; Bhattacharjee, Partha S.
Abstract: CD13/APN (aminopeptidase N) was first identified as a selective angiogenic marker expressed in tumor vasculature and is considered a target for anti-cancer therapy. CD13 was also reported to express in non-diabetic, hypoxia-induced retinal neovascularization. Whether diabetes induces upregulation of CD13 expression in the retina is unknown. We hypothesize that at an early stage of non-proliferative diabetic retinopathy (NPDR) characterized by disruption of blood-retinal barrier (BRB) permeability is related to upregulated expression of CD13 because of its known role in extracellular matrix (ECM) degradation. The purpose of this study is to evaluate the role of CD13/APN and the therapeutic efficacy of a CD13/APN inhibitor in a mouse model of streptozotocin-induced NPDR. Hyperglycemic C57Bl/6 mice 26 weeks after streptozotocin (STZ) injection were intravitreally injected with a sustained release formulation of CD13/APN inhibitor bestatin. At 15th day of post-bestatin treatment, mouse retinas were evaluated for vascular permeability by Evans blue dye extravasation assay, fluorescent angiography of retinal vascular permeability and leukostasis. Retinal protein extracts were analyzed by Western blot to determine the effects of bestatin treatment on the expression of CD13/APN related inflammatory mediators of ECM degradation and angiogenesis. Intravitreal bestatin treatment significantly inhibited retinal vascular permeability and leukostasis. This treatment also significantly inhibited retinal expression of CD13, ECM degrading proteases (heparanase and MMP9 and angiogenic molecules (HIF-1α and VEGF). Intravitreal CD13 inhibition may relate to furthering our knowledge on the protective effect of bestatin against diabetic retinal vasculature abnormalities through inhibition of retinal permeability, leukostasis, inflammatory molecules of ECM degradation and angiogenesis.